Crataegus sinaica defatted methanolic extract ameliorated monosodium iodoacetate-induced oxidative stress andinhibited inflammation in a rat model of osteoarthritis - Ifat A. Alsharif; Reham M. Abd-Elsalam; Mohammed S. Amer; Ahmed H. El-Desoky; Rehab F. Abdel-Rahman (Wolters Kluwer Medknow Publications, 2022)
Background and purpose: Osteoarthritis is a degenerative joint disease without definite treatment. It is characterized by intra-articular inflammation, cartilage degeneration, subchondral bone remodeling, and joint pain. The objective of the current study was to assess the anti-osteoarthritic effect and the possible underlying mechanism of action of Crataegus sinaica extract (CSE). Experimental approach: Intra-articular injection of monosodium iodoacetate in the right knee joint of all rats was done except for the sham group. One week later, the anti-inflammatory efficacy of CSE (100, 200, 300 mg/kg, daily p.o) for 4 successive weeks versus ibuprofen (40 mg/kg, p.o) was assessed. Serum inflammatory cytokines; as well as weekly assessment of knee joint swelling, joint mobility, and motor coordination were done. At the end of the experiment, a histopathological investigation of the affected knee joints and an x-ray investigation were also executed. Findings / Results: CSE significantly decreased joint swelling, pain behaviors, and serum levels of TNF-α, IL6, hyaluronic acid, and CTX-II. The radiographic findings revealed almost normal joint space with normal radiodensity and diameter in CSE-treated rats. As well, the histopathological and immunohistochemical investigations of the knee joints in CSE-treated groups retained the cartilage structure of knee joints. A significant reduction in the percentage of caspase-3-stained chondrocytes and a decrease in TGF-β1 immuno-positive areas in the synovial lining and sub lining were recorded in CSE-treated rats, compared to the osteoarthritis control group. Conclusion and implications: This study approved the chondroprotective effects of CSE, and its ability to inhibit the pain associated with osteoarthritis.